Hubungan Peran Dukungan Keluarga Dengan Kepatuhan Ibu Hamil Melakukan Pemeriksaan Kehamilan di PMB Setyaning Rahayu Dampit - Damaiyanti, Putri; Widya Keswara, Nila; Maulina, Rifzul (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Pregnancy is a vulnerable period for health. Efforts made by pregnant women to maintain the health of the fetus are ANC examinations. If ANC visits are not carried out properly, it will have an impact on the mother's health status, thereby increasing the maternal mortality rate. The factor that influences ANC adherence or visits is family support. Family support is very important to prevent unwanted conditions such as risky pregnancies, and this can be achieved by fulfilling complete antenatal care visits. The aim of this research is to determine the relationship between the role of family support and the compliance of pregnant women with pregnancy checks to increase K6 coverage at PMB Setyaning Rahayu. This type of study uses observational analytics with a cross sectional approach. The population of this research was all pregnant women who underwent examinations at PMB Setyaning Rahayu with a research sample of 31 pregnant women. Sampling used total sampling. Data analysis used the Chi-Square. The research results showed that 51.6% of pregnant women received good family support and as many as 61.3% were compliant in carrying out pregnancy checks. The results of the chi square test show that there is a relationship between the role of family support and the compliance of pregnant women with pregnancy checks to increase K6 coverage at PMB Setyaning Rahayu with a p-value of 0.015